Developing an interactive e-worksheet based on group investigation, integrating local wisdom to distinguish facts and opinions in informative texts - Diah Khoirunnafi'ah; Panca Dewi Purwati (Journal of Integrated Elementary Education, 2026)
This study aims to analyze the needs, media design, validity, feasibility, and effectiveness of the media to enhance elementary school students' reading literacy in distinguishing facts from opinions. This study used the ADDIE approach, with 9 fifth-grade students for limited testing and 16 students for field testing at the Muhammadiyah Ngadirejo Elementary School. Data collection was carried out through participatory observation, interviews, questionnaires, pre-test, and post-test. Addressing student passivity and difficulties in verifying facts and opinions, Gemini Ai was used to design interactive features of an e-worksheet integrating group investigation syntax and Temanggung local wisdom. Deemed very feasible across content, language, and display aspects, the media scored 96.43% from material experts and 93.75% from media experts. Additionally, the response rates from teachers and students were 88.33% and 92.22%, respectively, in the very practical category, while participatory observation showed a student activity score of 90.4%. The media proved to be effective (Sig. (2-tailed) = 0.000 < 0.05) with an N-Gain score of 0.69 in the limited trial and 0.68 in the field trial. These findings indicate that using Gemini Aito to develop an interactive e-worksheet based on group investigation and integrated with local wisdom is feasible, practical, and effective in improving grade V students' ability to distinguish opinions from facts in informative texts.